2020
DOI: 10.5114/hpc.2020.97897
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Physical Activity and Sports Consumption Habits in University Students

Abstract: Authors' contribution Wkład autorów: A. Study design/planning zaplanowanie badań B. Data collection/entry zebranie danych C. Data analysis/statistics dane-analiza i statystyki D. Data interpretation interpretacja danych E. Preparation of manuscript przygotowanie artykułu F. Literature analysis/search wyszukiwanie i analiza literatury G. Funds collection zebranie funduszy Summary Background. Adequate level of physical activity helps and provides optimal body function. Understanding the sports consumption and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Specifically, boys were more skilful in certain fine (i.e., fine manual control and its related subtests) and gross (i.e., body coordination, strength and agility and its related subtests) MSs. These results coincide with what has been reported that sex differences can strengthen a particular physical/MS [53][54][55]. in a widely cited investigation, Junaid and Fellowes [56] demonstrated that girls scored significantly higher than boys on visual motor and locomotor tasks, suggesting that girls attain manual dexterity earlier than boys.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, boys were more skilful in certain fine (i.e., fine manual control and its related subtests) and gross (i.e., body coordination, strength and agility and its related subtests) MSs. These results coincide with what has been reported that sex differences can strengthen a particular physical/MS [53][54][55]. in a widely cited investigation, Junaid and Fellowes [56] demonstrated that girls scored significantly higher than boys on visual motor and locomotor tasks, suggesting that girls attain manual dexterity earlier than boys.…”
Section: Discussionsupporting
confidence: 89%
“…Physical activity in the household was most positively and significantly correlated with quality of life [ 35 ]. It should be noted that women are more active in housework, and men are more active in their leisure time [ 36 ]. Housework comprises activities that result from daily duties.…”
Section: Discussionmentioning
confidence: 99%